Community Resource Governance in the Tribal Societies of Arunachal Pradesh - Gupta, Vishal (Indian Forester, 2005)
The indigenous tribal communities of Arunacbal Pradesh have been enjoying traditional rights over the forests and natural resources in their village boundaries. The customary laws have governed these relatively closed societies which were supplemented with the general policy of initial exclusion and later non-interference in their way of life. These societies have been practising Jhum for ages, a practice which is excoriated and repressed elsewhere in the country and the world, but taken as accepted here. The policy and legal framework also broadly supports the same and upholds their traditional rights. This paper attempts to bring forth the vario.us community management practices in these societies, describes the administrative and legal support for the same and traces the changes taking place in the traditional systems of community resource governance.